Grit, Student Academic Achievement and Factors Affecting It - Ihan Martoyo; Lindawati Lindawati (Jurnal Psikologi Teori dan Terapan, 2023)
Grit has been shown to be a more influential predictor of success than mere cognitive ability. Research on Grit is still minimal in Indonesia and is often descriptive in nature and does not specifically target student academic achievement. This study aims to fill this gap to reveal the interaction between Grit and student academic achievement. In addition, several aspects of student life were also observed to see their influence on Grit, including length of study, the number of students’ work obligation hours, and the amount of social media/TV consumption. The research was conducted using the Grit Scale.  Purposive sampling was used to collect data from 763 students from the Faculty of Teacher College, Universitas Pelita Harapan, with an age range of 18-22 years from 3 years of class and 4 study programs. Correlation and regression results show that Grit is associated with student academic achievement (r=.14, p<.01), and can predict student academic achievement significantly (β=.14, p<.001). In addition, there was also an increase in Grit scores from the second, to the third, and the fourth-year students.  The amount of students’ work obligation was found to be a positive predictor of Grit, while the amount of social media/TV consumption was a negative predictor. The implications of this research and the factors that influence students’ Grit will be discussed further.   ABSTRAK  Gereget (inggris: Grit) telah ditunjukkan sebagai prediktor keberhasilan yang lebih berpengaruh daripada kemampuan kognitif semata. Namun demikian, penelitian tentang Gereget masih minim di Indonesia dan sering bersifat deskriptif dan tidak menyasar secara khusus ke prestasi akademis mahasiswa. Penelitian ini bertujuan mengisi celah ini untuk mengungkap interaksi antara Gereget dan prestasi akademis mahasiswa. Sebagai tambahan, beberapa aspek kehidupan mahasiswa juga diamati pengaruhnya terhadap Gereget, termasuk lama studi, jumlah pemenuhan jam wajib kerja mahasiswa, dan jumlah konsumsi media sosial/TV. Penelitian kuantitatif dilakukan dengan menggunakan Skala Gereget (Grit-Scale). Purposive sampling digunakan untuk mengambil data dari 763 mahasiswa Fakultas Pendidikan Guru, Universitas Pelita Harapan, dengan rentang umur 18-22 tahun yang berasal dari 3 tahun angkatan dan 4 program studi. Hasil korelasi dan regresi menunjukkan bahwa Gereget berhubungan dengan prestasi akademis mahasiswa (r=.14, p<.01), dan dapat memprediksi prestasi akademis mahasiswa secara signifikan (β=.14, p<.001). Selain itu, juga ditemukan peningkatan nilai Gereget dari mahasiswa tahun kedua, ke tahun ketiga dan keempat. Jumlah jam wajib kerja mahasiswa ditemukan sebagai prediktor positif terhadap Gereget, sedangkan jumlah konsumsi media sosial/TV adalah prediktor negatif. Implikasi penelitian ini dan faktor-faktor yang mempengaruhi Geregetnya mahasiswa akan didiskusikan lebih jauh.